THE EMBRYONIC OF PAWAS (Osteochilus hasselti C.V) WITH DIFFERENT TEMPERATURE - Nawir, M.; ', Sukendi; ', Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on March 2016 at the Hatchery and Breeding Laboratory at Fisheries and Marine Science Faculty, University of Riau. The research aim to observe the embryonic of pawas (Osteochilus hasselti C.V) with to test levels optimum of incubation temperature. The method used in this research is an experimental method and design used was Completely Randomized Design (CRD) with four treatments and three replications. The treatment used is P0I26 (hatching with incubation temperature 26°C), P1I28 (hatching with incubation temperature 28°C), P2I30 (hatching with incubation temperature 30°C), P3I32 (hatching with incubation temperature 32°C). The result obtained by the fasted deviding process contained in the treatments in P3I32 (hatching with incubation temperature 32°C) is 2-32 cell devision of cell is 1 hour 15 minutes, morula to gastrula is 4 hours 36 minutes and the formation of embryo until the eggs hatch shield takes 17 hours 45 minutes.Keywords : Pawas (Osteochilus hasselti C. V), Temperatures, eggs